Changes in Periodic Limb Movements of Sleep After the Use of Continuous Positive Airway Pressure Therapy: A Meta-Analysis - Lin, Tzu-Chao; Zeng, Bing-Yan; Wu, Meng-Ni; Chen, Tien-Yu; Chen, Yen-Wen; Yeh, Pin-Yang; Tseng, Ping-Tao; Hsu, Chung-Yao (Frontiers in Neurology, 2022)
Background: Both obstructive sleep apnea (OSA) and periodic limb movements of sleep (PLMS) are common in the sleep laboratory. The severity of OSA can be improved by using continuous positive airway pressure (CPAP). However, increasing evidence has shown an elevated periodic limb movement index (PLMI) in patients with OSA who use CPAP, although the pathophysiology is still unknown. This meta-analysis aimed to investigate changes in PLMS after using CPAP and the potential pathophysiology of these changes. Methods: Clinical trials in adult humans investigating the comorbidity between PLMS and CPAP were identified and analyzed under random-effect model meta-analysis. Results: This meta-analysis consisted of 14 studies comprising 2938 patients with OSA. The PLMI was significantly increased after using CPAP with a difference in means of 1.894 (95% confidence interval=0.651 to 3.138, p=0.003). Subgroup analysis showed that CPAP was only significantly associated with an increase in PLMI in the patients without PLMS at baseline (p=0.045) and in those with a baseline body-mass index (BMI) <30 kg/m2 (p=0.045). Under the use of CPAP, apnea-hypopnea index and arousal index were positively correlated with changes in PLMI. Conclusion: These characteristics may serve as qualitatively predictive indicators of changes in PLMI after CPAP usage. Further analysis of the quantitative relationship between PLMI and the predictive indicators may be warranted.